How does mindfulness training affect attention and penalty kick performance in university football player - Jiaqi Wu; Lixin Ai (PLoS ONE, 2025)
Athletes often struggle to maintain attentional focus and performance consistency under pressure, particularly during high-stakes tasks like penalty kicks. This study examined the effects of brief mindfulness training on visual attention behaviors and penalty kick performance among university football players under non-pressure and pressure conditions. The study comprises two experiments: Experiment 1 was conducted in non-pressure conditions, whereas Experiment 2 involved pressure condition. Each experiment involved 40 participants, who were randomly assigned to either the intervention group or the control group. The intervention group underwent 15 minutes of brief mindfulness training, while the control group engaged in 15 minutes of quiet sitting. Eye-tracking technology was used to measure fixation count and fixation duration during the penalty kick tasks. In non-stress conditions, the mindfulness group showed a significant increase in fixation duration and fixation count, with no change in penalty kick performance. In pressure conditions, the mindfulness group again showed significant gains in fixation duration and fixation count, but penalty kick scores did not significantly improve. Comparisons across stress conditions revealed that fixation duration improvements were larger under pressure, suggesting mindfulness may enhance attentional stability when athletes are under stress. In conclusion, brief mindfulness training can enhance visual attention behaviors in university football players, especially under pressure, by promoting sustained focus on task-relevant visual targets.